Persepsi Mahasiswa Terhadap Peran Dan Praktik Artificial Intelligence Akuntansi Di Indonesia - Chelsya Chelsya; Nastasya Cindy (STIE Amkop Makassar, 2025)
It is inevitable that most of our activities have been taken over by Artificial Intelligence technology. Artificial intelligence (Artificial Intelligence) has been widely applied by companies, ranging from small, medium to large scale businesses, one example is the application of AI in accounting bookkeeping. Artificial intelligence (AI) has a very significant role in shaping the future evolution of accounting. One of the benefits of AI is that it reduces routine work such as manual data entry, allowing accountants to focus on deeper analysis of accounting strategies. With the help of AI tools, accountants can manage large volumes of data with a high degree of accuracy, help in predicting financial trends, and ensure consistency and decisions based on accurate information summarized by AI. Some of the positive impacts/benefits of implementing AI in accounting are: (1) Automation of routine tasks and bookkeeping, (2) Reducing errors in the accounting process (recording to financial reports), (3) Customizing client services and reports (flexible), (4 ) Has a high level of security, especially in managing confidential financial data, (5) Makes it easy to use and integrates with existing systems in the company's accounting environment. The application of AI in accounting also has negative impacts such as: (1) Reducing the number of employees (increasing unemployment rates) due to being replaced by AI, (2) Increasing dependence on technology, (3) Skills gap. The author considers that it is very necessary to research how accounting students view the role of AI in accounting, considering that accounting students will later enter the world of work or start businesses that will definitely use AI in their work. However, students' views on AI are very important, because if accounting students do not prepare themselves, they could